A kind of thermal insulation and sound insulation mortar and its preparation method and application

By aminating the limestone and combining the use of glass fiber composite materials and modified silica, the mortar has been solved in terms of compressive strength, sound insulation performance and thermal conductivity, and efficient thermal insulation effect has been achieved.

CN119349927BActive Publication Date: 2025-03-18HUNAN QUNXIANG TECH DEV CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411951383.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-12-27
Publication Date
2025-03-18
Estimated Expiration
2044-12-27

AI Technical Summary

Technical Problem

The existing mortar has shortcomings in compressive strength, sound insulation performance and thermal conductivity, and cannot achieve good load-bearing, deformation and thermal insulation effects.

Method used

By aminating the limestone and combining the use of glass fiber composite materials and modified silica, the compressive strength and sound insulation performance of the mortar are improved through the synergistic effect of multi-components, while reducing the thermal conductivity.

Benefits of technology

The compressive strength and sound insulation performance of the mortar are significantly improved, while reducing the thermal conductivity, achieving efficient thermal insulation effect.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The present application belongs to the technical field of building materials, and specifically relates to a thermal insulation and sound insulation mortar and its preparation method and application. The present invention treats limestone with amino, and uses it together with glass fiber composite material and modified silica. Through the synergistic effect of multiple components, the compressive strength and sound insulation performance of the mortar are effectively increased, while the thermal conductivity is reduced to achieve efficient thermal insulation.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application belongs to the technical field of building materials, and specifically relates to a thermal insulation and sound insulation mortar and a preparation method and application thereof. Background Art

[0002] Traditional mortar is mainly made of cement, sand and water mixed in a certain proportion, and is used in construction processes such as masonry and plastering. In recent years, with the advancement of science and technology, a variety of functional mortars have emerged. They add special functional ingredients such as lightweight aggregates, thermal insulation materials, waterproofing agents, etc. on the basis of traditional mortars to enhance the specific properties of mortars. Polymer modified mortar has excellent impermeability, small elastic modulus, good water retention and good flame retardancy, and is widely used in repair, waterproofing, grouting, sealing, anti-corrosion and composite insulation systems. As a binder, polymer mortar binds fine aggregates together, which can significantly and effectively improve the brittleness of mortar and improve its impact resistance, flexural strength, corrosion resistance and weather resistance.

[0003] A Chinese patent (publication number CN115925363B) discloses a sound insulation mortar and its preparation method. The invention is made of the following raw materials by weight: 25-35 parts of cement, 0-30 parts of reinforcing aggregate; 15-20 parts of vitrified microspheres, 0-10 parts of ceramsite sand, 10-30 parts of fly ash floating beads, 1-8 parts of admixtures, 2-4 parts of hyperbranched ethylene glycol chitosan, 1-3 parts of graphene hollow nanofibers, and 1-2 parts of waste aramid fibers. Through the interaction between the raw materials, the sound insulation mortar has a significant sound insulation effect, is safe and environmentally friendly to use, has excellent mechanical and thermal insulation properties, low production cost, and good anti-cracking performance. However, the patent does not solve the shortcomings and deficiencies of the mortar in the prior art: (1) insufficient compressive strength, unable to achieve good load-bearing and deformation; (2) poor sound insulation performance, easily leading to environmental noise pollution; (3) too high thermal conductivity, unable to achieve good thermal insulation effect.

[0004] Therefore, providing a thermal insulation and sound insulation mortar, increasing the compressive strength and sound insulation performance of the mortar by introducing different modified components, and reducing the thermal conductivity to achieve efficient thermal insulation has become an urgent problem to be solved in the industry. Summary of the invention

[0005] In view of the above problems, the purpose of the present invention is to provide a thermal insulation and sound insulation mortar and its preparation method and application. By subjecting limestone to amino treatment and using it together with glass fiber composite materials and modified silica, the compressive strength and sound insulation performance of the mortar are effectively increased through the synergistic effect of multiple components, while reducing the thermal conductivity to achieve efficient thermal insulation.

[0006] To achieve the above object, the present invention provides the following technical solutions:

[0007] A first aspect of the present application provides a method for preparing a thermal insulation and sound insulation mortar, comprising the following steps:

[0008] Step S1: adding 10-15 parts of limestone and 4-6 parts of dodecyl phosphate to 120-140 parts of deionized water by weight, shaking at a constant temperature of 80-90° C. for 20-30 minutes, filtering, and drying to obtain an intermediate product; adding 10-15 parts of the intermediate product to 50-60 parts of anhydrous ethanol by weight, ultrasonically dispersing for 1-2 hours to obtain a suspension, adding 2-4 parts of DL-alanine to the suspension, heating to 70-80° C. and stirring for 1-2 hours, filtering, washing, and drying to obtain amination limestone;

[0009] Step S2: by weight, 220-240 parts of the amino limestone, 100-120 parts of epoxy resin, 16-20 parts of glass fiber composite material and 8-10 parts of wood fiber are mixed and stirred for 20-30 minutes, and then 280-300 parts of cement, 260-280 parts of river sand, 6-8 parts of modified silica and 2-4 parts of additives are added and stirred for 40-60 minutes to obtain thermal insulation and sound insulation mortar;

[0010] The particle size of the limestone is 50-100 μm;

[0011] The preparation method of the glass fiber composite material comprises: mixing 40-60 parts of capric acid and 20-40 parts of palmitic acid by weight, stirring at 60-70° C. for 2-4 hours, then adding 8-10 parts of expanded perlite and vacuum impregnating for 40-60 minutes to obtain acidified expanded perlite; adding 2-4 parts of polydimethylsiloxane to 80-100 parts of toluene and mixing evenly, then adding 8-10 parts of the acidified expanded perlite and stirring for 10-20 minutes, then adding 20-30 parts of glass fiber and ultrasonically impregnating for 40-60 minutes, and drying to obtain the glass fiber composite material;

[0012] The diameter of the glass fiber is 4-6 μm;

[0013] The preparation method of the modified silica comprises: adding 140-160 parts of silica, 40-50 parts of liquid natural rubber, 4-6 parts of maleic anhydride and 2-4 parts of azobisisobutyronitrile to 460-500 parts of 1,4-dioxane by weight, stirring and reacting at 50-60° C. for 24-30 hours, washing with dichloromethane after the reaction is completed, filtering and drying to obtain the modified silica;

[0014] The particle size of the silicon dioxide is 200-400 nm.

[0015] Amination limestone can form hydrogen bonds through silicates, aluminates, etc. in the hydration products of amino cement, thereby enhancing the interfacial adhesion between limestone particles and cement matrix, improving the stability of the overall structure, and reducing the generation and development of microcracks at the interface, thereby improving the compressive strength of the mortar.

[0016] In some embodiments of the present application, the epoxy resin is a bisphenol A epoxy resin and a biphenyl epoxy resin; the mass ratio of the bisphenol A epoxy resin to the biphenyl epoxy resin is (1~2):1.

[0017] By compounding bisphenol A epoxy resin and biphenyl epoxy resin and keeping the mass ratio within a limited range, it is possible to ensure that the epoxy system of the thermal insulation and sound insulation mortar is well combined with other components, thereby ensuring good compressive strength and sound insulation performance, while reducing the thermal conductivity.

[0018] The glass fiber in the composite material can increase the internal damping of the mortar, allowing the material to absorb heat when subjected to temperature changes and convert it into other forms of energy, thereby reducing heat transfer by increasing damping; while the porous structure of the expanded perlite requires heat to pass through multiple tortuous paths during the transfer process, increasing the resistance to heat conduction, and the combined effect reduces the thermal conductivity of the mortar.

[0019] The surface of modified silica is grafted with rubber particles. The sound waves transmitted from the outside will first come into contact with the rubber particles and part of their energy will be absorbed due to the damping effect. Then they will be transmitted to the inside and come into contact with silica. Silica contains a large number of closed bubbles, which can effectively reflect and scatter sound waves and reduce the penetration of sound. The rubber provides high damping and elasticity, and the silica provides a porous structure and sound-absorbing effect, which effectively improves the sound insulation performance of the mortar.

[0020] In some embodiments of the present application, the auxiliary agent is selected from any one or a combination of at least two of cellulose ether, starch ether and redispersible latex powder.

[0021] The second aspect of the present application provides a thermal insulation and sound insulation mortar prepared by the method described in the first aspect.

[0022] The third aspect of the present application provides the use of the thermal insulation and sound insulation mortar prepared by the method described in the first aspect in the field of building materials.

[0023] Compared with the prior art, the present application at least achieves the following technical effects:

[0024] (1) The amino limestone of the present invention is combined with the epoxy resin through the amino group, and the glass fiber composite material introduces carboxyl groups through decanoic acid and palmitic acid to react with the epoxy groups of the epoxy resin. The modified silica introduces acid anhydride during the grafting modification and is compounded with the epoxy system. With the epoxy resin as the basis, a high-density interconnected network is constructed, which effectively improves the compressive strength of the mortar, reduces the thermal conductivity, and achieves a good sound insulation effect.

[0025] (2) The amino limestone of the present invention can form hydrogen bonds through silicates, aluminates, etc. in the hydration products of amino cement, thereby enhancing the interfacial adhesion between limestone particles and cement matrix, improving the stability of the overall structure, and reducing the generation and development of microcracks at the interface, thereby improving the compressive strength of the mortar.

[0026] (3) The glass fiber in the composite material of the present invention can increase the internal damping of the mortar, so that the material absorbs heat when subjected to temperature changes and converts it into other forms of energy, thereby reducing heat transfer by increasing damping; and the porous structure of the expanded perlite requires heat to pass through multiple tortuous paths during the transfer process, increasing the resistance to heat conduction, and the combined effect reduces the thermal conductivity of the mortar.

[0027] (4) The surface of the modified silica of the present invention is grafted with rubber particles. The sound waves transmitted from the outside will first come into contact with the rubber particles and part of their energy will be absorbed due to the damping effect, and then will be transmitted to the inside and come into contact with the silica. The silica contains a large number of closed bubbles, which can effectively reflect and scatter sound waves and reduce the penetration of sound. The rubber provides high damping and elasticity, and the silica provides a porous structure and sound-absorbing effect, which effectively improves the sound insulation performance of the mortar. DETAILED DESCRIPTION

[0028] In order to make the purpose, technical solution and advantages of the present invention more clear, the present invention is further described in detail below. However, it should be understood that the description herein is only used to explain the present invention and is not used to limit the scope of the present invention.

[0029] Unless otherwise defined, all technical terms and scientific terms used herein have the same meaning as those generally understood by those skilled in the art of the present invention, and the terms used in the specification of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present invention. The reagents and instruments used herein are all commercially available, and the characterization means involved can refer to the relevant descriptions in the prior art, which will not be repeated herein.

[0030] The sources of some components in the embodiments and comparative examples are as follows:

[0031] Cement, product number CA-75, was purchased from Zhengzhou Kerui (Group) Refractory Materials Co., Ltd.;

[0032] River sand, item number 5768, was purchased from Lingshou County Zehong Mineral Products Processing Plant;

[0033] Limestone I, with a particle size of 75 μm, was purchased from Xuzhou Tianhe Limestone Powder Sales Co., Ltd.;

[0034] Limestone II, with a particle size of 500 μm, was purchased from Southwest Petroleum University Jinniu Petroleum Technology Co., Ltd.;

[0035] Limestone III, particle size 5 μm, purchased from Hebei Lixin Chemical Co., Ltd. Jinling Branch;

[0036] Bisphenol A epoxy resin, product number jER828EL, was purchased from Mitsubishi Chemical Corporation;

[0037] Biphenyl type epoxy resin, product number NC-3000-L, purchased from Nippon Kayaku Co., Ltd.

[0038] Glass fiber I, model EMG-250, diameter 5 μm, purchased from Nanjing Glass Fiber Research and Design Institute;

[0039] Glass fiber II, model T435N, diameter 12 μm, purchased from Taishan Glass Fiber Co., Ltd.;

[0040] Wood fiber, item number mzxw-01, was purchased from Nanchang Xinchao Chemical Co., Ltd.;

[0041] Silica I, product number zkky7767653-0135, particle size 300 nm, purchased from Beijing Zhongke Keyou Technology Co., Ltd.;

[0042] Silica II, product number S104597, particle size 15 nm, purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.;

[0043] Silica III, product number S118568, particle size 1 mm, purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.;

[0044] Cellulose ether, product number 24, was purchased from Hefei Hongrui Biotechnology Co., Ltd.;

[0045] Starch ether, brand CASUCOL301, purchased from Avibe International Trading (Shanghai) Co., Ltd.;

[0046] Redispersible latex powder, product number 8011, purchased from Langfang Feitai New Material Technology Co., Ltd.;

[0047] Dodecyl phosphate, CAS No. 12751-23-4, was purchased from Shanghai MacLean Biochemical Technology Co., Ltd.;

[0048] DL-alanine, CAS No. 302-72-7, was purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.;

[0049] Polydimethylsiloxane, CAS No. 9006-65-9, was purchased from Shanghai MacLean Biochemical Technology Co., Ltd.;

[0050] Decanoic acid, CAS No. 334-48-5, was purchased from Sinopharm Chemical Reagent Co., Ltd.;

[0051] Palmitic acid, CAS No. 57-10-3, was purchased from Sinopharm Chemical Reagent Co., Ltd.;

[0052] Expanded perlite, item number 18, purchased from Lingshou County Lingcheng Mineral Products Co., Ltd.;

[0053] Liquid natural rubber, model NBR-101, purchased from Shenzhen Masini Elastomer Co., Ltd.;

[0054] Maleic anhydride, CAS No. 108-31-6, was purchased from Sinopharm Chemical Reagent Co., Ltd.;

[0055] Azobisisobutyronitrile, CAS No. 78-67-1, was purchased from Sinopharm Chemical Reagent Co., Ltd.;

[0056] 1,4-Dioxane, CAS No. 123-91-1, was purchased from Shanghai MacLean Biochemical Technology Co., Ltd.

[0057] Example 1

[0058] This embodiment provides a method for preparing a thermal insulation and sound insulation mortar, comprising the following steps:

[0059] Preparation of glass fiber composite material: 60 parts of capric acid and 40 parts of palmitic acid are mixed by weight, stirred at 70°C for 2 hours, and then 10 parts of expanded perlite are added and vacuum impregnated for 60 minutes to obtain acidified expanded perlite; 4 parts of polydimethylsiloxane are added to 100 parts of toluene and mixed evenly, and then 10 parts of the acidified expanded perlite are added and stirred for 20 minutes, and then 30 parts of glass fiber I (with a diameter of 5 μm) are added and ultrasonicated for 60 minutes, and dried to obtain the glass fiber composite material.

[0060] Preparation of modified silica: In parts by weight, 160 parts of silica I (particle size 300 nm), 50 parts of liquid natural rubber, 6 parts of maleic anhydride and 4 parts of azobisisobutyronitrile are added to 500 parts of 1,4-dioxane, and stirred for reaction at 60°C for 24 hours. After the reaction is completed, the modified silica is washed with dichloromethane, filtered and dried to obtain the modified silica.

[0061] Step S1: adding 15 parts of limestone I (with a particle size of 75 μm) and 6 parts of dodecyl phosphate to 140 parts of deionized water, shaking at a constant temperature of 90° C. for 30 minutes, filtering, and drying to obtain an intermediate product; adding 15 parts of the intermediate product to 60 parts of anhydrous ethanol, dispersing by ultrasonic for 2 hours to obtain a suspension, adding 4 parts of DL-alanine to the suspension, heating to 80° C. and stirring for 1 hour, filtering, washing, and drying to obtain an amination limestone;

[0062] Step S2: In parts by weight, 240 parts of the amino limestone, 120 parts of epoxy resin (80 parts of bisphenol A epoxy resin and 40 parts of biphenyl epoxy resin), 20 parts of glass fiber composite material and 10 parts of wood fiber are mixed and stirred for 30 minutes, and then 300 parts of cement, 280 parts of river sand, 8 parts of modified silica and 4 parts of auxiliary cellulose ether are added and stirred for 60 minutes to obtain thermal insulation and sound insulation mortar.

[0063] Example 2

[0064] This embodiment provides a method for preparing a thermal insulation and sound insulation mortar, comprising the following steps:

[0065] Preparation of glass fiber composite material: 40 parts of capric acid and 20 parts of palmitic acid are mixed by weight, stirred at 60°C for 4 hours, and then 8 parts of expanded perlite are added and vacuum impregnated for 60 minutes to obtain acidified expanded perlite; 2 parts of polydimethylsiloxane are added to 80 parts of toluene and mixed evenly, and then 8 parts of the acidified expanded perlite are added and stirred for 10 minutes, and then 20 parts of glass fiber I (with a diameter of 5 μm) are added and ultrasonicated for 40 minutes, and dried to obtain the glass fiber composite material.

[0066] Preparation of modified silica: In parts by weight, 140 parts of silica I (particle size 300 nm), 40 parts of liquid natural rubber, 4 parts of maleic anhydride and 2 parts of azobisisobutyronitrile are added to 460 parts of 1,4-dioxane, and stirred for reaction at 50° C. for 30 hours. After the reaction is completed, the mixture is washed with dichloromethane, filtered and dried to obtain the modified silica.

[0067] Step S1: by weight, 10 parts of limestone I (with a particle size of 75 μm) and 4 parts of dodecyl phosphate are added to 120 parts of deionized water, and the mixture is shaken at a constant temperature of 80° C. for 30 minutes, filtered, and dried to obtain an intermediate product; by weight, 10 parts of the intermediate product are added to 50 parts of anhydrous ethanol, and ultrasonically dispersed for 2 hours to obtain a suspension, 2 parts of DL-alanine are added to the suspension, the suspension is heated to 70° C. and stirred for 2 hours, and the amination limestone is obtained after suction filtration, washing, and drying;

[0068] Step S2: In parts by weight, 220 parts of the amino limestone, 100 parts of epoxy resin (50 parts of bisphenol A epoxy resin and 50 parts of biphenyl epoxy resin), 16 parts of glass fiber composite material and 8 parts of wood fiber are mixed and stirred for 20 minutes, and then 280 parts of cement, 260 parts of river sand, 6 parts of modified silica and 2 parts of auxiliary starch ether are added and stirred for 40 minutes to obtain thermal insulation and sound insulation mortar.

[0069] Example 3

[0070] This embodiment provides a method for preparing a thermal insulation and sound insulation mortar, comprising the following steps:

[0071] Preparation of glass fiber composite material: 50 parts of capric acid and 30 parts of palmitic acid are mixed by weight, stirred at 65°C for 3 hours, and then 9 parts of expanded perlite are added and vacuum impregnated for 50 minutes to obtain acidified expanded perlite; 3 parts of polydimethylsiloxane are added to 90 parts of toluene and mixed evenly, and then 9 parts of the acidified expanded perlite are added and stirred for 15 minutes, and then 25 parts of glass fiber I (with a diameter of 5 μm) are added and ultrasonicated for 50 minutes, and dried to obtain the glass fiber composite material.

[0072] Preparation of modified silica: In parts by weight, 150 parts of silica I (particle size 300 nm), 45 parts of liquid natural rubber, 5 parts of maleic anhydride and 3 parts of azobisisobutyronitrile are added to 480 parts of 1,4-dioxane, and stirred for reaction at 55° C. for 28 hours. After the reaction is completed, the modified silica is washed with dichloromethane, filtered and dried to obtain the modified silica.

[0073] Step S1: adding 12 parts of limestone I (with a particle size of 75 μm) and 5 parts of dodecyl phosphate to 130 parts of deionized water, shaking at a constant temperature of 85° C. for 25 minutes, filtering, and drying to obtain an intermediate product; adding 12 parts of the intermediate product to 55 parts of anhydrous ethanol, dispersing by ultrasonic for 2 hours to obtain a suspension, adding 3 parts of DL-alanine to the suspension, heating to 75° C. and stirring for 2 hours, filtering, washing, and drying to obtain an amination limestone;

[0074] Step S2: In parts by weight, 230 parts of the amino limestone, 110 parts of epoxy resin (70 parts of bisphenol A epoxy resin and 40 parts of biphenyl epoxy resin), 18 parts of glass fiber composite material and 9 parts of wood fiber are mixed and stirred for 25 minutes, and then 290 parts of cement, 270 parts of river sand, 7 parts of modified silica and 3 parts of auxiliary redispersible latex powder are added and stirred for 50 minutes to obtain thermal insulation and sound insulation mortar.

[0075] Comparative Example 1

[0076] This comparative example provides a method for preparing a thermal insulation and sound insulation mortar, which differs from Example 1 in that limestone I is used instead of amination limestone.

[0077] Comparative Example 2

[0078] This comparative example provides a method for preparing a thermal insulation and sound insulation mortar, which differs from Example 1 in that limestone II is used instead of limestone I to prepare the amino limestone.

[0079] Comparative Example 3

[0080] This comparative example provides a method for preparing a thermal insulation and sound insulation mortar, which is different from Example 1 in that limestone III is used instead of limestone I to prepare the amino limestone.

[0081] Comparative Example 4

[0082] This comparative example provides a method for preparing a thermal insulation and sound insulation mortar, which is different from Example 1 in that the amount of bisphenol A epoxy resin is changed to 100 parts, and the amount of biphenyl epoxy resin is changed to 20 parts.

[0083] Comparative Example 5

[0084] This comparative example provides a method for preparing a thermal insulation and sound insulation mortar, which is different from Example 1 in that the amount of bisphenol A epoxy resin is changed to 40 parts, and the amount of biphenyl epoxy resin is changed to 80 parts.

[0085] Comparative Example 6

[0086] This comparative example provides a method for preparing a thermal insulation and sound insulation mortar, which differs from Example 1 in that glass fiber I is used instead of glass fiber composite material.

[0087] Comparative Example 7

[0088] This comparative example provides a method for preparing a thermal insulation and sound insulation mortar, which is different from Example 1 in that glass fiber II is used instead of glass fiber I to prepare a glass fiber composite material.

[0089] Comparative Example 8

[0090] This comparative example provides a method for preparing a thermal insulation and sound insulation mortar, which differs from Example 1 in that silicon dioxide I is used instead of modified silicon dioxide.

[0091] Comparative Example 9

[0092] This comparative example provides a method for preparing a thermal insulation and sound insulation mortar, which differs from Example 1 in that silicon dioxide II is used instead of silicon dioxide I to prepare modified silicon dioxide.

[0093] Comparative Example 10

[0094] This comparative example provides a method for preparing a thermal insulation and sound insulation mortar, which differs from Example 1 in that silicon dioxide III is used instead of silicon dioxide I to prepare modified silicon dioxide.

[0095] The performance of the thermal insulation and sound insulation mortar prepared in the above examples and comparative examples was tested, and the specific testing method is as follows:

[0096] (1) Compressive strength test

[0097] The test was carried out with reference to the requirements of "JC / T 984-2011 Polymer Cement Waterproof Mortar".

[0098] (2) Thermal conductivity test

[0099] The test was carried out with reference to the requirements of JG / T 266-2011 Foamed Concrete.

[0100] (3) Impact sound insulation performance test

[0101] The test was carried out with reference to the requirements of GB / T 19889.6-2005 Acoustic sound insulation measurement of buildings and building elements Part 6: Laboratory measurement of impact sound insulation of floor slabs.

[0102] The performance test results are shown in Table 1:

[0103] Table 1 Performance test results

[0104]

[0105] It can be seen from the above performance test results that Examples 1-3 have good effects, with a compressive strength (28d) of 55.7~56.8MPa, a thermal conductivity of 0.071~0.078W / (m·K), and an impact sound insulation performance of 54~57 decibels; this is because the present invention, through the amino treatment of limestone, is used in conjunction with glass fiber composite materials and modified silica, and through the synergistic effect of multiple components, effectively increases the compressive strength and sound insulation performance of the mortar, while reducing the thermal conductivity to achieve efficient thermal insulation.

[0106] The comparative examples, however, did not adopt the necessary technical solutions, resulting in significantly worse performance tests than the examples. Compared with Example 1, Comparative Example 1 uses limestone I to replace the amino limestone, which reduces the compressive strength, increases the thermal conductivity, and deteriorates the impact sound insulation performance; Compared with Example 1, Comparative Example 2 uses limestone II to replace limestone I to prepare the amino limestone. Since the particle size of limestone II is too large, the modification effect is not good, which reduces the compressive strength, increases the thermal conductivity, and deteriorates the impact sound insulation performance; Compared with Example 1, Comparative Example 3 uses limestone III to replace limestone I to prepare the amino limestone. Since the particle size of limestone III is too small, the modification effect is not good, which reduces the compressive strength, increases the thermal conductivity, and deteriorates the impact sound insulation performance. The strength is reduced, the thermal conductivity is increased, and the impact sound insulation performance is deteriorated; compared with Example 1, the amount of bisphenol A epoxy resin in Comparative Example 4 is changed to 100 parts, and the amount of biphenyl epoxy resin is changed to 20 parts. Due to the excessive amount of bisphenol A epoxy resin, the compounding effect is not good, the compressive strength is reduced, the thermal conductivity is increased, and the impact sound insulation performance is deteriorated; compared with Example 1, the amount of bisphenol A epoxy resin in Comparative Example 5 is changed to 40 parts, and the amount of biphenyl epoxy resin is changed to 80 parts. Due to the small amount of bisphenol A epoxy resin, the compounding effect is not good, the compressive strength is reduced, the thermal conductivity is increased, and the impact sound insulation performance is deteriorated. The strength is reduced, the thermal conductivity is improved, and the impact sound insulation performance is deteriorated; compared with Example 1, Comparative Example 6 uses glass fiber I to replace the glass fiber composite material, the compressive strength is reduced, the thermal conductivity is improved, and the impact sound insulation performance is deteriorated; compared with Example 1, Comparative Example 7 uses glass fiber II to replace glass fiber I to prepare the glass fiber composite material. Since the diameter of glass fiber II is too large, the modification effect is not good, the compressive strength is reduced, the thermal conductivity is improved, and the impact sound insulation performance is deteriorated; compared with Example 1, Comparative Example 8 uses silicon dioxide I to replace modified silicon dioxide, then The compressive strength is reduced, the thermal conductivity is increased, and the impact sound insulation performance is deteriorated; compared with Example 1, Comparative Example 9 uses silica II to replace silica I to prepare modified silica. Since the particle size of silica II is too small, the modification effect is not good, the compressive strength is reduced, the thermal conductivity is increased, and the impact sound insulation performance is deteriorated; compared with Example 1, Comparative Example 10 uses silica III to replace silica I to prepare modified silica. Since the particle size of silica III is too large, the modification effect is not good, the compressive strength is reduced, the thermal conductivity is increased, and the impact sound insulation performance is deteriorated.

[0107] The applicant declares that the present application is explained through the above-mentioned embodiments, but the present application is not limited to the above-mentioned embodiments, that is, it does not mean that the present application must rely on the above-mentioned embodiments to be implemented. The technicians in the relevant technical field should understand that any improvement to the present application, the equivalent replacement of the raw materials of the product of the present application, the addition of auxiliary components, the selection of specific methods, etc., all fall within the scope of protection and disclosure of the present application.

[0108] The preferred embodiments of the present application are described in detail above; however, the present application is not limited to the specific details in the above embodiments. Within the technical concept of the present application, a variety of simple modifications can be made to the technical solution of the present application, and these simple modifications all fall within the protection scope of the present application.

[0109] It should also be noted that the various specific technical features described in the above specific embodiments can be combined in any suitable manner without contradiction. In order to avoid unnecessary repetition, this application will not further describe various possible combinations.

Claims

1. A method for preparing a thermal insulation and sound insulation mortar, characterized in that: The following steps are involved: Step S1: adding 10 to 15 parts of limestone and 4 to 6 parts of dodecyl phosphate to 120 to 140 parts of deionized water by weight, shaking at a constant temperature of 80 to 90° C. for 20 to 30 minutes, filtering, and drying to obtain an intermediate product; adding 10 to 15 parts of the intermediate product to 50 to 60 parts of anhydrous ethanol by weight, ultrasonically dispersing for 1 to 2 hours to obtain a suspension, adding 2 to 4 parts of DL-alanine to the suspension, heating to 70 to 80° C. and stirring for 1 to 2 hours, filtering, washing, and drying to obtain amination limestone; Step S2: by weight, 220 to 240 parts of the amino limestone, 100 to 120 parts of epoxy resin, 16 to 20 parts of glass fiber composite material and 8 to 10 parts of wood fiber are mixed and stirred for 20 to 30 minutes, and then 280 to 300 parts of cement, 260 to 280 parts of river sand, 6 to 8 parts of modified silica and 2 to 4 parts of additives are added and stirred for 40 to 60 minutes to obtain a thermal insulation and sound insulation mortar; The particle size of the limestone is 50 to 100 μm; The preparation method of the glass fiber composite material comprises: mixing 40 to 60 parts of capric acid and 20 to 40 parts of palmitic acid by weight, stirring at 60 to 70° C. for 2 to 4 hours, then adding 8 to 10 parts of expanded perlite and vacuum impregnating for 40 to 60 minutes to obtain acidified expanded perlite; adding 2 to 4 parts of polydimethylsiloxane to 80 to 100 parts of toluene and mixing evenly, then adding 8 to 10 parts of the acidified expanded perlite and stirring for 10 to 20 minutes, then adding 20 to 30 parts of glass fiber and ultrasonically treating for 40 to 60 minutes, and drying to obtain the glass fiber composite material; The diameter of the glass fiber is 4 to 6 μm; The preparation method of the modified silica comprises: adding 140 to 160 parts of silica, 40 to 50 parts of liquid natural rubber, 4 to 6 parts of maleic anhydride and 2 to 4 parts of azobisisobutyronitrile to 460 to 500 parts of 1,4-dioxane by weight, stirring and reacting at 50 to 60° C. for 24 to 30 hours, washing with dichloromethane after the reaction is completed, filtering and drying to obtain the modified silica; The particle size of the silicon dioxide is 200 to 400 nm; The epoxy resin is bisphenol A epoxy resin and biphenyl epoxy resin; the mass ratio of the bisphenol A epoxy resin to the biphenyl epoxy resin is (1-2):

1.

2. The method for preparing a thermal insulation and sound insulation mortar according to claim 1, characterized in that: The auxiliary agent is selected from any one of cellulose ether, starch ether and redispersible latex powder or a combination of at least two thereof.

3. A thermal insulation and sound insulation mortar, characterized in that: Prepared according to the method according to any one of claims 1 to 2.

4. Application of the thermal insulation and sound insulation mortar prepared by the method according to any one of claims 1 to 2 in the field of building materials.

Citation Information

Patent Citations

  • A sound-insulating mortar and its preparation method

    CN115925363B

  • Thermal insulation mortar and production method thereof

    CN106316259A

  • Low-carbon light-weight sound insulation mortar containing wood fibers as well as preparation method and application of low-carbon light-weight sound insulation mortar

    CN118791262A